Assessment of glycemic control among Tunisian diabetic adults. (20th October 2021) - Cherif, I; Rejaibi, S; Ben Mansour, N; Zoghlami, N; Saidi, O; Skhiri, A; Ben Slama, F; Ben Romthane, H; Turki, Z; Aounallah-Skhiri, H
Abstract: Background: Diabetes, a major public health issue in Tunisia, is responsible of an increased burden of morbidity and premature mortality. Achieving a good glycemic control is essential for reducing the morbidity-mortality associated with this disease. The purpose of our study was to assess the proportion of uncontrolled diabetes (UD) among Tunisian diabetic adults and assess associated factors. Methods: A national household survey, stratified at three degrees, was conducted in 2016. As part of this study, we included previously diagnosed diabetic adults aged 20 years or above. Sociodemographic data and medical history were collected using an individual questionnaire, and glycated hemoglobin (HbA1C) was measured using the "A1C Now +" device. The UD was defined based on the American Diabetes Association criteria for the year 2016 (HbA1c ≥7%). Multiple logistic regression model was used to determine factors associated with UD. Adjusted Odds Ratios (AOR) were presented with 95% confidence intervals (CI). All data analysis was performed using SPSS software. Results: A total of 873 subjects were included with a median age of 61 years and a sex-ratio equal to 0.9. The proportion of UD was (72.8%, 95% CI: [69.1-76.3]). In multivariate analysis, UD was more frequent among rural areas residents (AOR=1.8 [1.1-2.7]), those who had never seen a doctor within the year preceding the survey (AOR=2.2 [1.1-4.2]) and among those on oral antidiabetics (AOR=6.1 [1.9-18.9]) or insulin (AOR=23.8 [7.1-79.8]) compared to those who were following a diabetic diet. Conclusions: This study highlighted a very high proportion of UD in diabetic Tunisian adults. A better involvement of primary care physicians in overall patient care, and improved availability of antidiabetic drugs for patients, are strongly recommended. Key messages: Majority of Tunisian diabetic adults aged 20 years or older had an uncontrolled diabetes. Improving patient education and the availability of antidiabetic drugs for diabetic individuals in primary healthcare facilities is essential.